Investigating the Effect of Supervisor-Subordinate Guanxi on Innovative Work Behavior and the Mediation of Psychological Ability - Wasan Kamil Afloog (International Journal of Economics and Management Sciences, 2025)
The objective of this investigation is to investigate the implication of administrator-affiliate communication on innovative act moral and the mediation of psychological competence (the investigation community consists of occupationholders of Diwaniye Municipality. The investigation manner is practical in Conditions of objective and expressive and survey in Conditions of conducting manner. The statistical society includes all the occupationholders in Diwaniya municipality, whose number is 180, and in instruction to characterize the sample size, Cochran's formula was utilizated, and 123 people were randomly scaled. The data collection manner was a questionnaire tool, and the administrator-affiliate guanxi questionnaire was utilizated by Scandora and Grain (1984), Kanter's innovative act moral (1988), and psychological capability by Thomas and Wolthaus (1990). After compiling the initial frameact, coefficient analysis was done to obtain the accuracy of the structure. Cronbach's alpha coefficient was utilizated to scale the relicapability of the questionnaire. Then, all the proposed hypotheses were tested and analyzed using the structural equation figureing technique and using smart pls software, and the findings showed that the implication of administrator-affiliate guanxi on innovative act moral and the mediation of psychological capcapability of Diwaniya Municipality occupationholders has a remarkable implication.